2023
DOI: 10.18502/ijph.v52i2.11879
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Patellofemoral Pain Exhibiting Decrease Vertical Ground Reaction Force Compared to Healthy Individuals during Weight Bearing Tasks: A Systematic Reviews and Meta-Analysis

Abstract: Background: Vertical ground reaction force (VGRF) can lead to the development knee osteoarthritis. This review systematic and meta-analysis aimed to investigate the VGRF in patellofemoral pain patients (PFP) during weight bearing tasks. Methods: Search strategy was conducted in databases: Science Direct, Scopus, PubMed and Google Scholar from Sep 2020 to Jun 2021. The VGRF components we measured were passive impact (Fz1)/peak and propulsion/active peak (Fz2). The quality of the studies was evaluated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Google Scholar was used as a complementary search engine. In addition, a manual search in the relevant journals was performed to identify articles that may not have been identified in the electronic database search [7]. The search strategy was based on the patient, intervention, comparison, and outcome (PICO) index (Table 1).…”
Section: Search Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…Google Scholar was used as a complementary search engine. In addition, a manual search in the relevant journals was performed to identify articles that may not have been identified in the electronic database search [7]. The search strategy was based on the patient, intervention, comparison, and outcome (PICO) index (Table 1).…”
Section: Search Strategymentioning
confidence: 99%
“…Foot pronation in the initial stance phase is responsible for the response to loading and force attenuation during impact [7]. In a meta-analysis, Ahmadi (2022) reported that PFP patients tend to increase the loading rate [24].…”
Section: Hart Et Al 2020 [19]mentioning
confidence: 99%
See 1 more Smart Citation